Evaluating amenity access of new and repurposed housing within the 15-Minute City framework in Amsterdam - Esma Selen Aksoy; Titus Venverloo; Tom Benson; Fabio Duarte (Discover Cities)
Abstract Amsterdam has a housing shortage issue. To address this, the Municipality aims to provide 73,660 housing units by 2028, either by constructing new housing buildings or by repurposing existing buildings with other functions such as offices, schools or industrial spaces. The comparison between these two strategies in past research primarily focuses on lower construction costs, reduced raw material usage, and decreased energy consumption associated with demolition and new construction processes; on the other hand, comparisons of locational characteristics between new and repurposed housing projects have seldom been studied. In this paper, we compare access to amenities, specifically the number and diversity, between new and repurposed housing buildings based on their location in the city. Using the 15-Minute City concept as both a theoretical framework and a practical tool, we evaluate the amenities within a 15-min walking isochrone for 38,061 housing units (554 residential buildings) constructed between 2015 and 2019. By aggregating these results at district level, we deepen the analysis and provide insights that could support the development of locally tailored policies.